Problem Statement

Given an integer nn, prove that 3n+23n+2 is odd if and only if 9n+59n+5 is even.

Proof

If and only if statements can be broken down into two separate statements. We will first prove that if 3n+23n+2 is odd, then 9n+59n+5 is even. Then we will prove that if 9n+59n+5 is even, then 3n+23n+2 is odd. This is sufficient for pp if and only if qq.


Case 1 (contradiction)

Prove that for a given integer nn, if 3n+23n+2 is odd, then 9n+59n+5 is even

Suppose for the sake of contradiction that 3n+23n+2 is even. Then by definition there exists some integer kk such that 3n+2=2k3n+2=2k and it follows that n=2k23n = \frac{2k-2}{3} and

9n+5=9(2k23)+5=3(2k2)+5=2(3k3)+5\begin{align*} 9n+5 &= 9(\frac{2k-2}{3}) + 5 \\ &= 3(2k-2) + 5 \\ &= 2(3k-3) + 5 \end{align*}

and the term (3k3)(3k-3) is just an integer we will denote tt. It follows that

9n+5=2t+59n+5 = 2t + 5

It is a proven fact that the sum of an even integer and an odd integer is an odd integer. Notice how we have an odd term plus an even term on the right side of our equation. It follows that 9n+59n+5 is odd.

Here, we have reached a contradiction as 9n+59n+5 is odd when 3n+23n+2 is even. Therefore, if 3n+23n+2 is odd, then 9n+59n+5 is even.


Case 2 (contradiction)

Prove that for a given integer nn, if 9n+59n+5 is even the 3n+23n+2 is odd

Suppose for the sake of contradiction that 9n+59n +5 is odd. Then by definition 9n+5=2k+19n+5 = 2k+1 for some integer kk. It follows that n=2k49n =\frac{2k-4}{9} and

3n+2=3(2k49)+2=2(3k63)+2\begin{align*} 3n+2 &= 3(\frac{2k-4}{9}) + 2 \\ &= 2(\frac{3k-6}{3}) + 2 \end{align*}

notice how the term (3k63)(\frac{3k-6}{3}) is some integer we will denote tt. It follows that

3n+2=2t+2 3n+2 = 2t + 2

It is a proven fact that the sum of two even integers is an even integer. Notice how the two terms on the right are both even. It follows that 3n+23n+2 is even.

Here we have reached a contradiction as 3n+23n+2 is even when 9n+59n+5 is odd. Therefore, if 9n+59n+5 is even, then 3n+23n+2 is odd


Conclusion

Proving 3n+23n+2 is odd when 9n+59n+5 is even and 9n+59n+5 is even when 3n+23n+2 is odd is sufficient for 3n+23n+2 is odd if and only if 9n+59n+5 is even for a given integer kk

\blacksquare

Problem Statement

We say a function f:RRf : \mathbb{R} \rightarrow \mathbb{R} is bijective (or invertible) if for any yRy \in \mathbb{R} there exists a unique xRx \in \mathbb{R} such that f(x)=yf(x) = y.

Proof

Let yRy \in \mathbb{R}, we will prove that there exists a unique element xRx \in \mathbb{R} such that f(x)=2x+1=yf(x) = 2x + 1 = y.

Let x=y12x = \frac{y - 1}{2}, then

f(x)=2(y12)+1=y1+1=yf(x) = 2\left(\frac{y - 1}{2}\right) + 1 = y - 1 + 1 = y

Now suppose there exists another number zRz \in \mathbb{R} such that f(z)=yf(z) = y. Then f(z)=f(x)f(z) = f(x) so

2z+1=2x+1    2z=2x    z=x2z + 1 = 2x + 1 \implies 2z = 2x \implies z = x

Therefore, xx is unique. In conclusion, there exists a unique xRx \in \mathbb{R} such that f(x)=2x+1=yf(x) = 2x + 1 = y for any yRy \in \mathbb{R}, so f(x)f(x) is bijective.

\blacksquare

Problem Statement

Let a,b,ca,b,c be three real numbers and let mm be their average so m=(a+b+c)3m = \frac{(a+b+c)}{3}. Prove that at least one of a,b,ca,b,c is less than or equal to mm

Proof (contradiction)

Let a,b,ca,b,c be three real numbers. Let mm denote the average of a,b,ca,b,c so m=(a+b+c)3m = \frac{(a+b+c)}{3}.

For the sake of contradiction suppose a,b,ca,b,c are all strictly greater than mm. Therefore,

a>mb>mc>m\begin{align*} a &> m \\ b &> m \\ c &> m \\ \end{align*}

Summing these together we see that

a+b+c>m+m+ma+b+c>3ma+b+c3>m\begin{align*} a + b + c &> m + m + m \\ a + b + c &> 3m \\ \frac{a + b + c}{3} &> m \end{align*}

Here we have a contradiction as mm is the average and must equal (a+b+c)3\frac{(a + b + c)}{3}. Therefore, at least one of the real numbers a,b,ca,b,c is less than or equal to mm.

\blacksquare

Problem Statement

Suppose there are two integers xx and yy. Prove using the contrapositive statement that if x2(y+3)x^{2} * (y+3) is even then x is even or y is odd

Proof (contrapositive)

We will prove this statement by proving its contrapositive.

Contrapositive Statement: If xx is an odd integer and yy is an even integer, then x2(y+3)x^2(y + 3) is odd.

Suppose there is some odd integer xx and some even integer yy. By definition, there exist integers aa and kk such that x=2a+1x = 2a + 1 and y=2ky = 2k.

Substituting for xx and yy respectively:

x2(y+3)=(2a+1)2(2k+3)=(4a2+4a+1)(2k+3)=(8a2k+8ak+2k)+(12a2+12a+3)=2(4a2k+4ak+k+6a2+6a+1)+1\begin{align*} x^{2}(y+3) &= (2a + 1)^{2} * (2k + 3) \\ &= (4a^2 + 4a + 1) * (2k + 3) \\ &= (8a^2k + 8ak + 2k) + (12a^2 + 12a + 3) \\ &= 2(4a^2k + 4ak + k + 6a^2 + 6a +1) + 1 \end{align*}

Now, notice that the term (4a2k+4ak+k+6a2+6a+1)(4a^2k + 4ak + k + 6a^2 + 6a +1) is an integer we will denote jj. Thus x2(y+3)=2j+1x^{2}(y + 3) = 2j + 1 for some integer jj. By definition, x2(y+3)2x^{2}(y+3)^2 is an odd integer.

We have shown that when xx is an odd integer and yy an even integer, x2(y+3)x^2(y + 3) is odd. Therefore, we have proven the contrapositive, which is equivalent to proving the original statement. Therefore, x2(y+3)x^{2} * (y+3) is even when xx is even or yy is odd.

\blacksquare

Problem Statement

A perfect square is an integer nn for which there exists an integer kk such that n=k2n = k^2. We aim to prove that if nn is a positive integer such that (n2mod4)(n \equiv 2 \mod 4) or (n3mod4)(n \equiv 3 \mod 4), then nn is not a perfect square.

Proof (contrapositive)

We will prove the above statement by proving its contrapositive:

Contrapositive Statement: If nn is a positive integer and nn is a perfect square, then nn mod four does not equal two and nn mod four does not equal 3.

Suppose nn is some positive integer and nn is a perfect square. It follows by the definition of a perfect square that there exists an integer kk such that n=k2n = k^2.

We will consider two cases when kk is even and when kk is odd.


Case 1 (k is even)

Suppose k=2ak = 2a for some integer aa. Then, n=k2=(2a)2=4a2n = k^2 = (2a)^2 = 4a^2 nn is divisible by four, hence nmod4=0n \mod 4 = 0.


Case 2 (k is odd)

Suppose k=2a+1k = 2a + 1 for some integer aa. Then, n=k2=(2a+1)2=4a2+4a+1=4(a2+a)+1n = k^2 = (2a + 1)^2 = 4a^2 + 4a + 1 = 4(a^2 + a) + 1 nn will always be one greater than a number divisible by four. Therefore, dividing nn by four will result in a remainder of one.


Conclusion

With these two cases, we have shown that for any positive integer nn that is a perfect square, nn mod four does not equal two and nn mod four does not equal 3. Therefore, we have proven the contrapositive statement, which is equivalent to proving the original statement. It follows that if nn is a positive integer such that (n2mod4)(n \equiv 2 \mod 4) or (n3mod4)(n \equiv 3 \mod 4), then nn is not a perfect square.

\blacksquare

Problem Statement

We aim to prove by contrapositive that if aa and bb are integers such that 4(a2+b2)4|(a^2 + b^2), then aa and bb must both be even.

Proof (contrapositive)

We will prove the above statement by proving its contrapositive:

Contrapositive Statement: Let aa and bb denote two integers. If aa or bb are odd, then 4(a2+b2)4 \nmid (a^2 + b^2).

Suppose aa is odd. Then by definition, there exists some integer kk such that a=2k+1a = 2k + 1. It follows:

(a2+b2)=((2k+1)2+b2)=(4k2+4k+1+b2)=(4(k2+k)+1+b2)(a^2 + b^2) = ((2k + 1)^2 + b^2) = (4k^2 + 4k + 1 + b^2) = (4(k^2 + k) + 1 + b^2)

We see that when aa is an odd integer, four does not divide a2a^2 and leaves a remainder of one. When aa is odd, we have two possible cases that follow: bb is either even or odd.

Case 1 (b is even)

Suppose bb is an even integer. Then by definition, there exists some integer tt such that b=2tb = 2t. It follows that:

(a2+b2)=((2k+1)2+(2t)2)=(4k2+4k+1+4t2)=4(k2+k+t2)+1 (a^2 + b^2) = ((2k + 1)^2 + (2t)^2) = (4k^2 + 4k + 1 + 4t^2) = 4(k^2 + k + t^2) + 1

We see that there will always be a remainder of one. Therefore, when aa is odd and bb is even, four does not divide (a2+b2)(a^2 + b^2).

Case 2 (b is odd)

Suppose bb is an odd integer. Then by definition, there exists some integer tt such that b=2t+1b = 2t + 1. It follows that:

(a2+b2)=((2k+1)2+(2t+1)2)=(4k2+4k+1+4t2+1)=4(k2+k+t2)+2 (a^2 + b^2) = ((2k + 1)^2 + (2t + 1)^2) = (4k^2 + 4k + 1 + 4t^2 + 1) = 4(k^2 + k + t^2) + 2

We see that there will always be a remainder of two. Therefore, when aa is odd and bb is odd, four does not divide (a2+b2)(a^2 + b^2).

We have shown that if aa is an odd integer, it is sufficient for 4(a2+b2)4 \nmid (a^2 + b^2).

The same argument holds if we had initially assumed bb to be an odd integer, resulting in the exact same conclusions.

Therefore, we have proven the contrapositive statement: if aa or bb are odd integers, then 4(a2+b2)4 \nmid (a^2 + b^2). It follows that if aa and bb are integers such that 4(a2+b2)4|(a^2 + b^2), then aa and bb must both be even.

\blacksquare

Problem Statement

Let a,b,c,da, b, c, d be natural numbers such that

1a+1b+1c+1d=1\frac{1}{a} + \frac{1}{b} + \frac{1}{c} + \frac{1}{d} = 1

We aim to prove that at least one of the numbers a,b,c,da, b, c, d is even.

Proof (contradiction)

We suppose, for the sake of contradiction, that the natural numbers a,b,c,da, b, c, d are all odd and

1a+1b+1c+1d=1\frac{1}{a} + \frac{1}{b} + \frac{1}{c} + \frac{1}{d} = 1

By manipulating the given equality, we see that

1=1a+1b+1c+1d=b+aab+d+ccd=cd(b+a)+ab(d+c)abcd=(cdb+cda)+(abd+abc)abcd1 = \frac{1}{a} + \frac{1}{b} + \frac{1}{c} + \frac{1}{d} = \frac{b + a}{ab} + \frac{d + c}{cd} = \frac{cd(b+a) + ab(d+c)}{abcd} = \frac{(cdb + cda) + (abd + abc)}{abcd}

It is known that the product of any two odd numbers is odd, and the sum of any two odd numbers is even.

We observe that the terms cdcd and abab are the product of two odd numbers, which is odd. When distributing the terms over (b+a)(b + a) and (d+c)(d + c) respectively, we are multiplying two odd numbers together: (cd)b,(cd)a,(ab)d,(ab)c(cd)b, (cd)a, (ab)d, (ab)c, which is odd. The sum of two odd numbers is even.

Therefore, there exist some integers kk and tt such that (cdb+cda)=2k(cdb + cda) = 2k and (abd+abc)=2t(abd + abc) = 2t.

We see that the term in the denominator abcdabcd is the product of all odd numbers, therefore abcdabcd is odd and by definition abcd=2n+1abcd = 2n + 1 for some integer nn. Therefore,

1=(cdb+cda)+(abd+abc)abcd=2(k+t)2n+11 = \frac{(cdb + cda) + (abd + abc)}{abcd} = \frac{2(k + t)}{2n + 1}

Multiplying both sides by 2n+12n + 1, we reach the following equality:

(2n+1)1=2(k+t)(2n + 1) * 1 = 2(k + t)

This equality says that the product of two odd numbers (2n+1)(2n+1) and 11 equals some even number 2(k+t)2(k + t). However, it is known that the product of two odd numbers is odd. Therefore, we have reached a contradiction, and at least one of the natural numbers a,b,c,da, b, c, d must be even.

\blacksquare

Problem Statement

Let rr be some nonzero rational number and yy be some irrational number. We aim to prove that the product of rr and yy is irrational.

Proof (contradiction)

Let rr be some nonzero rational number. Then by definition, there exist two integers pp and qq such that q0q \neq 0, gcd(pp,qq)=1= 1, and r=pqr = \frac{p}{q}.

Let yy be some irrational number. Then by definition, there exist no two integers nn and kk such that n0n \neq 0, gcd(nn,kk)=1= 1, and y=nky = \frac{n}{k}.

Suppose for the sake of contradiction that the product of yy and rr is rational. Therefore, by definition, ry=abr * y = \frac{a}{b} for two integers a,ba, b.

We know that rr is a rational nonzero number. It follows that

ry=ab,pqy=ab,y=aqbpr * y = \frac{a}{b}, \quad \frac{p}{q} * y = \frac{a}{b}, \quad y = \frac{aq}{bp}

We see that the terms aqaq and bpbp are integers denoted as uu and vv respectively. Therefore,

y=uvy = \frac{u}{v}

Here we have a contradiction. yy is irrational, and therefore no two integers n,kn,k exist such that y=nky = \frac{n}{k}. Thus, the product of a nonzero rational number and an irrational number must be irrational.

\blacksquare

Problem Statement

Let the notation n=abn = \overline{ab} represent a two-digit integer nn with digits aa and bb. We aim to prove that 3n3|n if and only if 3(a+b)3|(a+b).

Proof

Let k=abk = \overline{ab} represent a two-digit number with digits aa and bb. Then n=ab=10a+bn = \overline{ab} = 10a + b.

Let zz be an integer such that z=(a+b)z = (a + b).


Case 1 (\big(Proving if 3n3|n then 3(a+b))3|(a+b)\big)

Suppose 3n3|n, then n0mod3n \cong 0 \mod 3. Consider nz=ab(a+b)=(10a+b)(a+b)=9an - z = \overline{ab} - (a + b) = (10a + b) - (a + b) = 9a. We can see that 39a3|9a so 3(nz)3|(n - z). It follows by definition that znmod3z \cong n \mod 3, therefore z0mod3z \cong 0 \mod 3, so 3(a+b)3|(a+b).


Case 2 (\big(Proving if 3(a+b)3|(a+b) then 3n)3|n \big)

Suppose 3(a+b)3|(a+b), then (a+b)=z0mod3(a+b) = z \cong 0 \mod 3. Consider zn=(a+b)ab=(a+b)(10a+b)=9az - n = (a+b) - \overline{ab} = (a+b) - (10a+b) = -9a. We can see that 39a3|-9a so 3(zn)3|(z - n). By definition, nzmod3n \cong z \mod 3 and n0mod3n \cong 0 \mod 3, so 3n3|n.


In conclusion, we have shown that for n=abn = \overline{ab}, 3n3|n if and only if 3(a+b)3|(a+b).

\blacksquare

Problem Statement

Prove that there exists a unique function defined on R\mathbb{R} with values in R\mathbb{R} that satisfies f(x)=2xf'(x) = 2x and f(0)=3f(0) = 3.

Proof

Let f:RRf: \mathbb{R} \rightarrow \mathbb{R} be the function f(x)=x2+3f(x) = x^2 + 3. Then f(x)=2xf'(x) = 2x and f(0)=(0)2+3=3f(0) = (0)^2 + 3 = 3, so ff satisfies all desired properties.

We will now show that ff is unique. Suppose for the sake of contradiction that there exists a different function g:RRg: \mathbb{R} \rightarrow \mathbb{R} such that g(x)=2xg'(x) = 2x and g(0)=3g(0) = 3.

We will integrate g(x)g'(x) with respect to xx:

g(x)dx=g(x)=x2+c\int g'(x) \, dx = g(x) = x^2 + c

It follows that g(0)=c=3g(0) = c = 3 and g(x)=x2+3g(x) = x^2 + 3. Here we have reached a contradiction as we assumed f(x)g(x)f(x) \neq g(x). In conclusion, f(x)=x2+3f(x) = x^2 + 3 is the unique function satisfying f(x)=2xf'(x) = 2x and f(0)=3f(0) = 3.

\blacksquare